Our army : soldiers, politics, and American civil-military relations - Dempsey, Jason K., 1972- (Princeton University Press, 2010)
"Conventional wisdom holds that the American military is overwhelmingly conservative and Republican, and extremely political. Our Army paints a more complex picture, demonstrating that while army officers are likely to be more conservative, rank-and-file soldiers hold political views that mirror those of the American public as a whole, and army personnel are less partisan and politically engaged than most civilians"--Publisher's description